Eksplorasi In Silico Senyawa Fitokimia untuk Penghambatan Protein STAT3 dalam Mengatasi Resistensi Obat pada Kanker Payudara Triple Negatif - Dewi Hambar Sari; Sri Suciati Ningsih; Suryadi Islami (Jurnal Penelitian Pendidikan IPA, 2024)
Breast cancer is the most common cancer among women and a major cause of cancer-related death worldwide, including Indonesia. Triple-negative breast cancer (TNBC) is an aggressive subtype of breast cancer, characterized by high mortality and resistance to standard treatments. Cancer stem cells (CSCs) is known to be a key factor of drug resistance in TNBC, mediated by the signal tranducer and activator of transcription factor 3 (STAT3). This study aims to explore the bioactive compounds from Indonesian’s natural product which potentially target CSCs by inhibiting STAT3. We used in silico methods, consist of literature review, followed by selection of promising compounds, ADMET analysis and selection using Lipinski’s rules, and molecular docking simulation. Our results found curcumin, quercetin, α-mangostin, gingerol, and rocalglamide as the bioactive candidates which target CSCs. ADMET testing showed that only curcumin, quercetin, and gingerol meet the Lipinski’s criteria. The molecular docking results showed that quercetin exhibited the strongest binding affinity (-8.3 kcal/mol) compared to curcumin (-6.9 kcal/mol) and gingerol (-5.9 kcal/mol). The results indicate that quercetin binds effectively at the active site of STAT3. The findings suggest that quercetin has potential as a STAT3 inhibitor. Further research is needed to determine the significant efficacy and potential as an anticancer.